OBJECTIVES OF MONITORING AND CONTROLLING IN THE MANAGEMENT SYSTEM OF AGRIBUSINESS ENTERPRISES - NOSACH, Nataliia; YEHIOZARIAN, Artur (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article discusses the role of monitoring and controlling in the management of agribusiness enterprises, particularly in the context of dynamic development and globalization challenges. The aim of the study is to identify the main objectives of monitoring and controlling in the management system of agribusiness enterprises, as well as to develop scientifically grounded recommendations for integrating them into management practice to improve the efficiency and stability of agricultural enterprises. The study presents the basic principles of organizing monitoring and controlling, as well as justifying the need for using modern management tools to ensure the effective operation of agribusinesses. The article also provides an analysis of the main approaches to monitoring, emphasizing its importance in ensuring the stability and efficiency of production processes. It was found that monitoring in the agribusiness sector allows for the timely identification of deviations in key performance indicators and responds to changes in the external environment, including climatic conditions, market fluctuations, and changes in legislation. The study justifies the role of digital technologies and automated systems in improving the efficiency of data collection and processing, contributing to more accurate forecasting and timely decision-making. The article discusses how controlling tools help enterprises optimize cost processes, resource planning, and improve financial stability through the implementation of a management performance system (KPI). It was found that controlling systems provide feedback between different management levels, allowing management to adjust strategies and tactics in response to market changes. The research revealed that the use of monitoring and controlling tools is key to ensuring the sustainability of enterprises in conditions of uncertainty and constant changes in the external environment. In particular, organizing monitoring enables agribusiness enterprises to achieve high competitiveness by optimizing costs and resources, enhancing production efficiency, and minimizing the impact of negative factors. The study also emphasizes the importance of integrating monitoring and controlling into a unified management system. This promotes greater transparency of processes and ensures more effective communication between the enterprise’s departments, which is a critical aspect in agribusiness production. With this approach, enterprises can adapt more quickly to changes and achieve strategic goals.